Bone mineral density in patients with interstitial lung disease - Alhamad, Esam H; Nadama, Rufai (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Objective: To determine the prevalence of low bone mineral density (BMD) and the risk factors for osteoporosis in patients with interstitial lung disease (ILD). Methods: Consecutive newly diagnosed ILD patients (n=196) were included in the study. Detailed demographic and clinical data were collected at the time of diagnosis, along with BMD measurements. Univariate and multivariate logistic regression analyses were used to determine the risk factors for osteoporosis. Results: Forty-four percent of the patients had osteoporosis, and 36% had osteopenia. The diagnosis of usual interstitial pneumonia (UIP) was more frequently observed in the patients with osteoporosis than in those without osteoporosis (67 vs. 47%, respectively; p=0.005). The univariate analyses identified the following five variables that were associated with an increased risk of osteoporosis at any site: older age (odds ratios [OR], 1.06; 95% confidence intervals [CI], 1.04 - 1.09; p<0.0001), UIP diagnosis (OR, 2.39; 95% CI, 1.33 - 4.30; p=0.003), higher partial pressure of carbon dioxide (PaCO2) (OR, 1.08; 95% CI, 1.01 - 1.14; p=0.01), hypertension (OR, 1.92; 95% CI, 1.05 - 3.49; p=0.033) and diabetes mellitus (OR, 2.38; 95% CI, 1.25 - 4.56; p=0.008). However, older age was the only independent predictor of osteoporosis (adjusted OR, 1.05; 95% CI, 1.02 to 1.08; p=0.001). Conclusions: We observed a high prevalence of osteoporosis and osteopenia among newly diagnosed ILD patients. Our findings suggest that there is a substantially increased risk of osteoporosis and that early screening and aggressive treatment with various anti-bone resorptive therapies are necessary in ILD patients. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 151-159)